Plasma Membrane H+-ATPase in Maize Roots Induced for NO3- Uptake. - Santi, S. (1995)
Plasma membrane H+-ATPase was studied in maize (Zea mays L.) roots induced for NO3- uptake. Membrane vesicles were isolated by means of Suc density gradient from roots exposed for 24 h either to 1.5 mM NO3- or 1.5 mM SO4-. The two populations of vesicles had similar composition as shown by diagnostic inhibitors of membrane-associated ATPases. However, both ATP-dependent intravesicular H+ accumulation and ATP hydrolysis were considerably enhanced (60-100%) in vesicles isolated from NO3--induced roots. Km for Mg:ATP and pH dependency were not influenced by NO3- treatment of the roots. ATP hydrolysis in plasma membrane vesicles for both control and NO3--induced roots was not affected by 10 to 150 mM NO3- or Cl-. On the other hand, kinetics of NO3-- or Cl--stimulated ATP-dependent intravesicular H+ accumulation were modified in plasma membrane vesicles isolated from NO3-- induced roots. Immunoassays carried out with polyclonal antibodies against plasma membrane H+-ATPase revealed an increased steady-state level of the enzyme in plasma membrane vesicles isolated from NO3--induced roots. Results are consistent with the idea of an involvement of plasma membrane H+-ATPase in the overall response of roots to NO3-.